2011
DOI: 10.1017/cbo9780511844058
|View full text |Cite
|
Sign up to set email alerts
|

The Climate of Rebellion in the Early Modern Ottoman Empire

Abstract: The Climate of Rebellion in the Early Modern Ottoman Empire explores the serious and far-reaching impacts of Little Ice Age climate fluctuations in Ottoman lands. This study demonstrates how imperial systems of provisioning and settlement that defined Ottoman power in the 1500s came unraveled in the face of ecological pressures and extreme cold and drought, leading to the outbreak of the destructive Celali Rebellion (1595–1610). This rebellion marked a turning point in Ottoman fortunes, as a combination of ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(75 citation statements)
references
References 400 publications
2
64
0
5
Order By: Relevance
“…As described in Roberts et al (2012) aridity w1400e1900 AD during the LIA, with drought independently recorded in tree ring and historical sources from Anatolia 1580e1610 AD (Kuniholm, 1990;Touchan et al, 2007;White, 2011). Dd 18 O lakewater suggests a less seasonal climate at this time (zone 4).…”
Section: Implications For Near East Palaeoclimatologymentioning
confidence: 86%
“…As described in Roberts et al (2012) aridity w1400e1900 AD during the LIA, with drought independently recorded in tree ring and historical sources from Anatolia 1580e1610 AD (Kuniholm, 1990;Touchan et al, 2007;White, 2011). Dd 18 O lakewater suggests a less seasonal climate at this time (zone 4).…”
Section: Implications For Near East Palaeoclimatologymentioning
confidence: 86%
“…These last authors reported that the late 16th and early 17th centuries in Anatolia were characterized by political, social, and climatic instability, which caused a large-scale change in land use and large sudden fluctuations in urban populations. White (2011) has also linked various Little Ice Age sociopolitical crises in the Ottoman Empire to tree-ring-reconstructed drought.…”
Section: Dendroclimatology and Atmospheric Circulationmentioning
confidence: 99%
“…Particularly for the Balkans and Serbia, this was a critical period in terms of political, social, economic and demographic changes. After several major conflicts with regional kingdoms in the early 1500s, the Ottoman Empire conquered the Balkans and for almost the next 160e170 years, instituted a number of systems for the management and provisioning of resources for its territories, all the while directing the expansion of the settlement and cultivation across the region (White, 2011). Both 16 th and 17 th Century Balkans enjoyed a relatively peaceful period with noteworthy commercial progress and significant increase in population (McEvedy and Jones, 1978).…”
Section: Introductionmentioning
confidence: 99%